Coastal Zone Management Applications in Turkey - Samsunlu, A.; Tanik, A.; Maktav, D.; Akca, L.; Uslu, O. (Springer Netherlands, 2000)
Coastal zone management and protection are of utmost importance for countries with coastlines, primarily due to their significant tourism activities. Coastal zones are threatened by pollution from two types of sources, point and non-point. Point source pollution is from domestic and industrial waste, with the former producing a much greater volume during the summer tourist high season. Non-point sources come from agricultural activities, marine transportation, atmospheric deposition, urban run-off, and so forth. Coastal areas are important - 90% of all the countries in the world are coastal countries with 40% of the world’s population living there. If one defines a coastal zone as a 50 m wide strip of coastline, 50% of the world’s population is settled there [1, 2].